2009
DOI: 10.1002/qj.448
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of observations on a local numerical fog prediction system

Abstract: ABSTRACT:As poor visibility conditions have great influence on air traffic, a need exists for accurate, updated fog and low-cloud forecasts. COBEL-ISBA, a boundary-layer one-dimensional numerical model, has been developed for the very short-term forecasting of fog and low clouds. This forecasting system assimilates the information from a local observation system designed to provide details on the state of the surface boundary layer, as well as that of the fog and low-cloud layers. This article aims to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 12 publications
3
21
0
1
Order By: Relevance
“…The bias was also reduced in the lower part of the domain for temperature after 1 h of the forecast and for specific humidity over the whole domain after 1 h of the forecast. The smaller bias shows that the initialization of ISBA and the interface between COBEL and ISBA worked better with the new algorithm then with the operational set-up, since it was shown by previous studies (Rémy and Bergot, 2009) that a faulty initialization of ISBA is a cause of increasing forecast bias on temperature and specific humidity close to the ground. Figure 9 shows the RMSE of PART50 as a percentage of REF's RMSE for temperature and specific humidity, and also the bias difference between the two experiments for FOG.…”
Section: Near-fog Situationmentioning
confidence: 60%
See 2 more Smart Citations
“…The bias was also reduced in the lower part of the domain for temperature after 1 h of the forecast and for specific humidity over the whole domain after 1 h of the forecast. The smaller bias shows that the initialization of ISBA and the interface between COBEL and ISBA worked better with the new algorithm then with the operational set-up, since it was shown by previous studies (Rémy and Bergot, 2009) that a faulty initialization of ISBA is a cause of increasing forecast bias on temperature and specific humidity close to the ground. Figure 9 shows the RMSE of PART50 as a percentage of REF's RMSE for temperature and specific humidity, and also the bias difference between the two experiments for FOG.…”
Section: Near-fog Situationmentioning
confidence: 60%
“…Two sets of simulated observations were made: one for the study of clear-sky nights and of shallow-fog situations (NEAR-FOG), and the other for the study of frequent and deep fogs (FOG). (Rémy and Bergot, 2009, provide more details on how the simulated observations were generated. ).…”
Section: Simulated Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…is is why accurate forecasts of fog and haze have become an important issue. e observation [6,7] and modelling [8,9] of dense fog have been studied in recent years. Several dynamic, thermal, and water vapor conditions including the layered structure of thermal inversion, the increase of temperature in the ground layer after sunrise, and the vertical transmission of heat, momentum, and water vapor caused by turbulent mixing have been found that trigger to dense fog [1,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Observations are thus lacking for validating model simulations (Bergot, 2013). Real-time LWC observation could have a significant impact on fog predictions (Rémy and Bergot, 2009). In this work, the possibility of measuring the LWC with a lidar is based on the existence of a relationship between the LWC and the optical extinction in fogs.…”
Section: Introductionmentioning
confidence: 99%